(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Objective: Using the hydrophilic polymer polyethylene glycol 6000 (PEG 6000) and chitosan, the solid dispersion (SD) technique is used to increase the solubility and dissolution of perphenazine. Materials and Methods: SDs of perphenazine were prepared with polymers PEG 6000 and chitosan, using different methods of preparation: (1) Solvent evaporation and (2) dropping technique method along with different drug: carrier ratios. Performance of the prepared formulations was evaluated for solubility, Fourier transform infrared (FTIR) spectroscopy. Results: Perphenazine’s solubility was improved in all SDs. Both solubility and carrier concentration were positively correlated. When prepared using the dropping method, the concentration of the perphenazine- SD PPD2 1:2 demonstrated improved water solubility. Conclusion: According to the investigations, PEG 6000 and chitosan later form an amorphous state in SD, which FTIR confirms. The SD containing perphenazine (dropping method) demonstrated high solubility and drug release.